(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. La procedura costituzionale - 3. Il diritto penale - 4. I principî: a) la dignità … - 5. (segue) b) la coscienza … - 6. (segue) c) la separazione (ovvero la laicità). Presented uncostitutionality and justifiable assisted suicide: innovations in continuity ABSTRACT: For the first time the Italian Constitutional Court adopted a double ruling (anticipatory the one, deciding the other) in the same judicial review. And for the first time also elaborated the circumstances of a justifiable (doctor-) assisted suicide, that so far was in any case a crime. They are two outstanding jurisprudential innovations, however the aim of the Author is to demonstrate that they are not in break but in continuity with the decision techniques of the Court, on one hand, and the leading cases on the topic of criminal justifications, on the other hand. Particularly the concept of subjective dignity, that according to the Court is the reason behind the decision of the patient, is recurring in the precedents of the Court of Cassation. Generally, moreover, the concepts of conscience, life and death prevail on this matter, neverthless are differently interpreted according to an ethic, specially religious, perspective or a secular, specially state, perspective. The merit of the decision consists precisely of the separatist, secular planning between ethics and law.